Detection of IgG antibody against the porcine norovirus GII.11 in human, domestic and wild animals - Xu, Jiayi; Du, Huisha; Yu, Junxuan; Wu, Ruojun; Zhang, Yu; Lu, Qianxin; Jiang, Xin; Zeng, Bingwen; Li, Tianhui; Chen, Qing; Dai, Ying-Chun (Frontiers in Microbiology, 2025)
Zoonotic diseases pose a critical threat to global public health, with noroviruses (NoVs) increasingly recognized for their potential to cross species barriers. Traditionally, NoVs were considered host-specific; however, recent evidence suggests the possibility of interspecies transmission. This study investigates the zoonotic potential of porcine NoV (PorNoV) genotype GII.11, which shares high genetic similarity with human NoVs (HuNoVs), by detecting GII.11-specific IgG antibodies in humans and various animals using a Luciferase Immunosorbent Assay (LISA). Seroprevalence was observed in humans (15.2%), pigs (49.3%), dogs (30.6%), wild rats (9.5%), and bats (65.1%), marking the first detection of GII.11 PorNoV antibodies in humans and non-swine species. Bats exhibited the highest seropositivity and antibody levels [vs. humans (P = 0.0011) and pigs (P = 0.0164)], suggesting their potential role as reservoirs. These findings provide serological evidence for anthropozoonotic transmission, challenging the paradigm of strict host specificity in NoVs. Enhanced surveillance of PorNoV in animal reservoirs and high-risk human populations is needed to mitigate zoonotic spillover risks. Further research should aim to elucidate mechanisms of transmission and the clinical significance of cross-species NoVs exposure.